The Effect of Educational Intervention Based on the Theory of Planned Behavior on Degree of Optimism among Male High School Students - Alireza jafari Baghkheirati; Leila Ghahremani; Mohammad Hossein Kaveh; Sareh keshavarzi (Shiraz University of Medical Sciences, 2015)
Background: When people maintain positive attitudes during life, their beliefs orientation will be highly beneficial to their health. In other words, those who have optimistic expectations report better physical health which is the result of their better psychological compatibility. The present study aimed to investigate the effect of educational intervention based on Theory of Planned Behavior (TPB) on Shirazi male high school students' degree of optimism.Methods: This educational randomized controlled trial was conducted on 240 male high school students in Shiraz. The research sample was selected through multi-stage random sampling. In this study, a demographic information form was used to gather the students' demographic characteristics. Besides, a positive thinking researcher-made questionnaire was designed based on TPB. Moreover, the life orientation test (optimism scale) developed by Scheier and Carver was used to evaluate the participants' degree of optimism. After all, the data were analyzed in SPSS statistical software (v. 19) using descriptive and inferential methods. Significance level was set at 0.05 in all the tests.Results: Compared to the control group, all the constructs of TPB increased in the intervention group after the training (P<0.001). Moreover, Pearson correlation indicated a significant relationship between the constructs, and the highest correlation was among attitude, perceived behavioral control, and intention.Conclusion: According to the research findings, all the constructs of TPB played a key role in increasing the students' positive think. Thus, educational intervention based on TPB has a positive effect on increasing the students' positive think.